Social constructivism and the philosophy of science - Kukla, André, 1942- (London ; New York : Routledge, 2000)
Social constructionists maintain that we invent the properties of the world rather than discover them. Is reality constructed by our own activity? Do we collectively invent the world rather than discover it?André Kukla presents a comprehensive discussion of the philosophical issues that arise out of this debate, analysing the various strengths and weaknesses of a range of constructivist arguments and arguing that current philosophical objections to constructivism are inconclusive. However, Kukla offers and develops new objections to constructivism, distinguishing between the social causes.
Defining constructivism -- Constructivism and the sociology of scientific knowledge -- The varieties of dependence -- The varieties of constitutive constructivisms -- The empirical case for constructivism -- The a priori case for constructivism -- Three brief and inadequate objections to constructivism -- The problem of misrepresentation -- Constructive empiricism and social constructivism -- The infinite regress of constructions -- The Duhemian asymmetry -- The problem of the two societies -- Constructivism and time -- Constructivism and logic -- Relativism -- Semantic constructivism -- Irrationalism.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Science -- Philosophy; Constructivism (Philosophy); Constructivisme (Philosophie); SCIENCE -- Philosophy & Social Aspects; Constructivism (Philosophy); Science -- Philosophy; Konstruktivismus; Wissenschaftstheorie; Konstruktivismus; Konstruktivismus; Wetenschapsfilosofie; Kennissociologie; Constructivisme; Constructivisme (philosophie); Sciences -- Philosophie